Establishment of a Fosmid Library for Pseudorabies Virus SC Strain and Application in Viral Neuronal Tracing - Qi, Hansong; Wu, Hongxia; Abid, Muhammad; Qiu, Hua-Ji; Sun, Yuan (Frontiers in Microbiology, 2020)
Pseudorabies virus (PRV) is a member of Alphaherpesvirinae subfamily, its neurotropism and latency infection attracts the attention of many scientists. PRV tagged with a fluorescent reporter gene as a tracker has been used to analyze neuronal circuits, including anterograde and retrograde. In this study, we used fosmid library to construct a rapid and efficient platform to generate recombinant PRV. Firstly, the highly purified PRV SC genomic DNA was sheared randomly into approximately 30-49 kb DNA fragments. After end-blunting and phosphorylation, the DNA fragments were cloned into the fosmid vector and transformed into Escherichia coli. A total of 200 fosmids that cover the complete genome of PRV SC was sequenced. 13 fosmid combinations in 5 groups were transfected into Vero cells, respectively, and each group can successfully rescue PRV strain SC. There was no significant difference between wild type and recombinant in both morphology and growth kinetics. In the next step, an enhanced green fluorescent protein (EGFP) was fused into the amino-terminal of UL36 protein by Red/ET Recombination technology and recombinant rPRV SC-UL36-EGFP was rescued successfully. At last, the single viral particles with green fluorescent were monitored retrograde moving in the axon with average velocity 0.71+0.43 µm/s at 0.5-2 hpi, and anterograde moving with average velocity 0.75+0.49 µm/s at 8 hpi. Integration of fosmid library and Red/ET Recombination technology in our work was highly efficient and stable for constructing PRV recombinants. This study will accelerate understanding biology of PRV and the development of novel vaccines.